'Do I have to spell it out?' Dyslexia, Lexism, and an object of comparison. (6th April 2018) - Collinson, Craig
Abstract : In this article I mount an attack on the problematic conceptions of literacy that lie behind the Standards and Testing Agency's 2015 Interim Teacher Assessment Frameworks at the End of Key Stage 2 and the Key Stage 2 English Grammar, Punctuation and Spelling Tests . I employ an object of comparison (a philosophical method), for attitudes towards literacy and dyslexics. I challenge current conceptions of the Othering of, and discrimination against, dyslexics. I argue for the concept of 'Lexism' as an alternative explanatory account for the existence of dyslexics.